EXPERT SYSTEM FOR DIAGNOSING DISEASE USING FUZZY LOGIC - Jullia Titaley (Sam Ratulangi University, 2008)
In this research, a system for diagnosing disease was designed and implemented. This system will be used for paramedics expert. They need to enter many symptoms. The symptoms are classified into two categories, crisps and fuzzy. The fuzzy symptoms are input using slider. It is used for uncertainty symptoms. Building this system, needs three steps knowledge acquisition, knowledge representation and then building knowledge base, and finally building inference engine. This system uses standard class operator, algebraic class operator, and Einstein class operator. Implication rule uses Dienes-Rescher and for combine all rules use Mamdani Combination. Based on all symptom that have been entered using standard class operator, this system is a success for diagnosing disease and its inference value. Keywords : diagnose disease, expert system, fuzzy logic.